Factors influencing Malaysians’ halal knowledge in purchasing halal pharmaceutical products / Wan Nur Khaleda W. Hassan - W. Hassan, Wan Nur Khaleda (Faculty of Business and Management, 2020)
Halal pharmaceutical product is growing and flourishing in Malaysia. The demands are mostly from Muslims. In Islam, Muslims are required to only consume halal goods in order to get Allah’s blessings. Nevertheless, there are only a few pharmaceutical products available in the market with certified halal logo. Hence, for Muslim consumers in Malaysia, their personal effort includes the action of reading the ingredients on the packaging. However, for some consumers, the information on the products ingredients seem to be far beyond the consumer’s basic knowledge. This study was therefore conducted to examine the factors influencing Malaysians‟ halal knowledge in purchasing halal pharmaceutical products. Questionnaires were distributed and returned by 253 respondents. This study found that access to product information influence Malaysians‟ halal knowledge in purchasing halal pharmaceutical products.